Cocaine Gut: A Rare Case of Cocaine-Induced Esophageal, Gastric, and Small Bowel Necrosis - Lefika Bathobakae MD, MPH; Sacide S. Ozgur MD; Rammy Bashir MSc; Tyler Wilkinson MSc; Phenyo Phuu MD; Ruhin Yuridullah MD; Gabriel Melki MD; Jessica Escobar MLS; Sohail Qayyum MD (SAGE Publishing, 2024)
Cocaine is an indirect-acting sympathomimetic drug that inhibits norepinephrine and dopamine reuptake in the adrenergic presynaptic cleft. Cocaine use has been associated with strokes, angina, arrhythmias, and agitation. Data on gastrointestinal complications such as mesenteric ischemia, bowel necrosis, ulceration, and perforation are scarce. Here, we present a rare case of cocaine-induced esophageal, gastric, and small bowel necrosis that contributes to the limited literature on this subject. Diagnosis of cocaine-induced gastrointestinal complications involves a combination of imaging studies, laboratory assessments, and histopathological examinations. Timely surgical resection, supported by intravenous fluids, antibiotics, and pain management, is the mainstay of treatment. The prognosis varies but is significantly influenced by the promptness and effectiveness of the intervention, underscoring the importance of vigilant clinical care in such cases.